Prebiotics Supplementation Impact on the Reinforcing and Motivational Aspect of Feeding - Delbès, Anne-Sophie; Castel, Julien; Denis, Raphaël G. P.; Morel, Chloé; Quiñones, Mar; Everard, Amandine; Cani, Patrice D.; Massiera, Florence; Luquet, Serge H. (Frontiers in Endocrinology, 2018)
Energy homeostasis is tightly regulated by the central nervous system which respond to nervous and circulating inputs to adapt food intake and energy expenditure. However the rewarding and motivational aspect of food is tightly dependent of dopamine (DA) release in mesolimbic dopaminergic (MCL) and could be operant in uncontrolled caloric intake and obesity. Accumulating evidence indicate that manipulating the microbiota-gut-brain axis through prebiotic supplementation can have beneficial impact of the host appetite and body weight. However the consequences of manipulating the implication of the microbiota-gut-brain axis in the control motivational and hedonic/reinforcing aspects of food is still underexplored. In this study we investigate whether and how dietary prebiotic fructo-oligosaccharides (FOS) could oppose, or revert, the change in hedonic and homeostatic control of feeding occurring after a 2-months exposure to high-fat high sugar (HFHS) diet. The reinforcing and motivational components of food reward were assessed using a two food choice paradigm and a food operant behavioral test in mice exposed to FOS either during or after HFHS exposure. We also performed mRNA expression analysis for key genes involved in limbic and hypothalamic control of feeding. We show in a preventive like approach, FOS addition of HFHS diet had beneficial impact of hypothalamic neuropeptides, and decreased the operant performance for food but only after an overnight fast while it did not prevent the imbalance in mesolimbic markers for DA signaling induced by palatable diet exposure nor the spontaneous tropism for palatable food when given the choice. However, when FOS was added to control diet after chronic HFHS exposure, although it did not significantly alter body weight loss, it greatly decreased palatable food tropism and consumption and was associated with normalization of MCL markers for DA signaling. We conclude that the nature of the diet (regular chow or HFHS) as well as the timing at which prebiotic supplementation is introduced (preventive or curative) greatly influence the efficacy of the gut-microbiota-brain axis. This crosstalk selectively alters the hedonic or motivational drive to eat and triggers molecular changes in neural substrates involved in the homeostatic and non-homeostatic control of body weight.